2018
DOI: 10.1038/s41467-018-04098-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines cooperate with TNF to provide protective anti-viral immunity and to enhance inflammation

Abstract: The role of cytokines and chemokines in anti-viral defense has been demonstrated, but their relative contribution to protective anti-viral responses in vivo is not fully understood. Cytokine response modifier D (CrmD) is a secreted receptor for TNF and lymphotoxin containing the smallpox virus-encoded chemokine receptor (SECRET) domain and is expressed by ectromelia virus, the causative agent of the smallpox-like disease mousepox. Here we show that CrmD is an essential virulence factor that controls natural ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 75 publications
(108 reference statements)
3
33
0
Order By: Relevance
“…We have recently demonstrated that CrmD is an essential virulence factor for ECTV, which causes mousepox, a smallpox-like disease in mouse. In addition, we showed that both CrmD activities, anti-TNF and antichemokine, are required for a successful evasion of the host immune response by ECTV (27).…”
mentioning
confidence: 90%
“…We have recently demonstrated that CrmD is an essential virulence factor for ECTV, which causes mousepox, a smallpox-like disease in mouse. In addition, we showed that both CrmD activities, anti-TNF and antichemokine, are required for a successful evasion of the host immune response by ECTV (27).…”
mentioning
confidence: 90%
“…In this work, we aimed to investigate the presence of these cells in different clinical forms of dengue infection. Because IL10 + Th1 may also express other cytokines besides IL10 and IFNγ, 32 we decided also to investigate the production of tumor necrosis factor (TNF), a cytokine that possesses anti‐viral properties 33 and has also been found in a subpopulation of T‐cells producing IFNγ simultaneously during DENV infections 30,31 . Therefore, in this work, we evaluated dengue patients for the presence of DENV‐specific T‐cells producing IFNγ, TNF and/or IL10 at defervescence (critical) and convalescence phases of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of TNF by soluble TNF inhibitors including receptors and different monoclonal antibodies is an effective therapeutic strategy widely used for the treatment of RA and other inflammatory conditions [39]. During viral infection, concomitant blockade of both TNF and a reduced set of chemokines by a single secreted protein was found to completely abrogate local inflammation in the mousepox intradermal infection model, effectively ablating the host response to produce a lethal infection [19]. Strikingly, both TNF and chemokine inhibition were found to be required for this effect, which may reflect the local crosstalk between both signaling pathways as well as the cell types that produce and respond to them.…”
Section: Discussionmentioning
confidence: 99%
“…While the SECRET domain can be found independently in three different viral proteins, it was shown to act in concert with the TNF-binding moieties in CrmD and CrmB, which are thus effectively bispecific cytokine inhibitors. Importantly, in vivo experiments using the mousepox model showed that both TNF-and CK-blocking activities are important determinants of virulence and have complementary roles in the control of local inflammation during infection [19].…”
Section: Introductionmentioning
confidence: 99%